Sequential precipitation induced interdiffusion: a general strategy to synthesize microtubular materials for high performance lithium ion battery electrodes. Issue 38 (21st September 2018) - Chen, Fei; Zhang, Weixin; Fu, Junrui; Yang, Zeheng; Fan, Xiaoming; Zhang, Weibo; Chen, Zhangxian; Huang, Mengqiu; Yang, Shihe
Abstract : A general sequential precipitation induced non-equilibrium interdiffusion method gives access to a series of LiNi x Co y Mn1− x − y O2 microtube materials. Abstract : 1D hollow structures are of great interest for wide applications, owing much to their kinetic transport advantages, but their facile synthesis through rational design remains a key challenge. In this work, we report for the first time a sequential precipitation induced interdiffusion strategy to synthesize a series of tubular electrode materials by the lithium impregnation and annealing of tube-like oxalate precursors. Different from conventional Ostwald ripening-induced mass migration within a single component, here the sequential precipitation is designed to promote non-equilibrium interdiffusion between different components, thus hollowing out the core. We show the wide scope of this strategy by rationally designing hollow electrode materials of multi-metal oxides. In particular, the syntheses of the most promising high energy cathode materials, Ni-rich LiNi0.8 Co0.1 Mn0.1 O2 and Li-rich Li1.2 Ni0.13 Co0.13 Mn0.54 O2 microtubes, have been demonstrated, which deliver excellent electrochemical performance in terms of the initial coulombic efficiency, reversible capacity, rate capability and cycling stability.